Domestic component level analysis for multipurpose autonomous robot - Vita Susanti; Henny Sudibyo; Ridwan Arief Subekti; Ghalya Pikra; Rakhmad Indra Pramana; Andri Joko Purwanto; Merry Indahsari Devi; Agus Fanar Syukri; Roni Permana Saputra (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2021)
Multipurpose autonomous robot technology has been developed to assist transportation sectors or the current emergency as the Covid-19 pandemic. A practical issue in the robotic industry concerns the domestic content in commodities, services, and a combination of goods and services commonly determined as domestic component level (DCL). To be considered a standardized national product, a product's DCL must surpass a certain level of local content composition. This research aims to investigate the DCL of a developed multipurpose autonomous robot in Indonesia called ROM20. The research was initiated by interviewing specialists in DCL calculation and robotics research to perform DCL analysis on ROM20. The next step was breaking down the ROM20 components into a second layer component, in which the amount of domestic component and overseas components can be derived. Finally, the ROM20 DCL value was calculated by dividing the cost of domestic components by the total cost of domestic and overseas components. As a digital product, the ROM20 DCL calculation result showed that the manufacturing aspect is 70 %, and the development aspect is 30 %. The overall ROM20 DCL value has been calculated as 52.23 %, which surpasses the national standard threshold at 40 % DCL value. Therefore, ROM20 can be considered a high-value standardized national product, impacting the competitiveness of local products and the fast-growing medical device industry in Indonesia.